The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1155/2021/8640794
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the COVID‐19 Mortality Rate with a New Versatile Modification of the Log‐Logistic Distribution

Abstract: The goal of this paper is to develop an optimal statistical model to analyze COVID-19 data in order to model and analyze the COVID-19 mortality rates in Somalia. Combining the log-logistic distribution and the tangent function yields the flexible extension log-logistic tangent (LLT) distribution, a new two-parameter distribution. This new distribution has a number of excellent statistical and mathematical properties, including a simple failure rate function, reliability function, and cumulative distribution fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The log-logistic distribution has been used to model mortality data ( Muse et al, 2021 ), so we also consider it: where is a location parameter and σ > 0 is a shape parameter. Like the log-normal distribution, we also use 2- and 3-mixtures of log-logistic distributions ( Puente-Ajovín et al, 2020a ): where 0 ≤ p 1 , 1 − p 1 ≤ 1, and where 0 ≤ p 1 , p 2 , 1 − p 1 − p 2 ≤ 1.…”
Section: Methodsmentioning
confidence: 99%
“…The log-logistic distribution has been used to model mortality data ( Muse et al, 2021 ), so we also consider it: where is a location parameter and σ > 0 is a shape parameter. Like the log-normal distribution, we also use 2- and 3-mixtures of log-logistic distributions ( Puente-Ajovín et al, 2020a ): where 0 ≤ p 1 , 1 − p 1 ≤ 1, and where 0 ≤ p 1 , p 2 , 1 − p 1 − p 2 ≤ 1.…”
Section: Methodsmentioning
confidence: 99%
“…e ExEW distribution is compared to submodels such as the W, EE [41], and EW distributions [16], and other common lifetime distributions including the log-logistic (LL), beta Weibull (BW) [14], beta extended Weibull (BEW) [43], modified beta Weibull (MBW) [44], and tan-loglogistic (TanLL) distributions [45]. e competing models' pdfs are as follows:…”
Section: Applications To Real-life Datamentioning
confidence: 99%
“…The generalised Lindley distribution was first introduced in 2011 by Nadarajah et al, who showed that it outperforms gamma, log-normal, Weibull, and exponential distributions when taking bathtub hazard rate into account [12]. In 2021, Mahmood et al [19] published an enlarged Cosine generalised family of distributions for dependability modelling: characteristics and applications with simulation analysis, and Muse et al [20] suggested a new flexible form of the loglogistic distribution. Citations [5], [17], and [6] in 2022 explored a family of produced distributions with applications.…”
Section: Introductionmentioning
confidence: 99%